Traffic Safety of Older Drivers in Various Types of Road Intersections - Tomaž Tollazzi; Marko Renčelj; Vlasta Rodošek; Borut Zalar (Promet (Zagreb), 2010)
In industrialized countries people over 50 years of age represent a rapidly growing part of population. Their lifestyle is also becoming more active, which means that the percentage of older drivers in the population of all drivers is also increasing. Many different studies have shown that elderly drivers are more frequently involved in specific types of accidents, especially at intersections. In the past 15 years there was a trend of increasing popularity of roundabouts in Slovenia. Their introduction was generally supported by the arguments of increased traffic-flow capacity and traffic safety as well. The studies on which these arguments are based were performed with an “ideal” type of driver in mind; the one that fully understands new rules and reacts correctly in all situations that may occur at such intersections, where there are no light signals to guide them. An elderly person does not necessarily conform to that ideal and if the percentage of elderly drivers became significant, the premises of the above mentioned studies may not be correct anymore which in turn implies that their results could also be questioned. The present study concentrated on the evaluation of traffic safety of elderly drivers, at various types of intersection, from their own perspective. Various statistical analyses of obtained data were performed. The most important finding was that we may claim, with high degree of probability, that the average person of the age of over 60 feels more unsafe at double-lane roundabouts than they would feel had the same intersection been equipped with traffic lights. Elderly traffic participants will always cause more accidents or participate in them due to hazardous factors. Challenge, arising from many different studies and researches, is in studying what measures and solutions can reduce the risk for elderly participants. KEYWORDS: traffic safety, road intersections, roundabouts, elderly people, older drivers